A Development of Textile Fabric Homogeneity Based on Computational Physics (Image Processing) with MATLAB - Valentinus Galih Vidia Putra; Andrian Wijayono; Cahaya Rosyidan; Juliany Ningsih Mohamad (Jurnal Fisika FLUX, 2020)
The textile industry is currently moving towards to the fourth Industrial Technological Revolution. One of the applications of the industrial revolution 4.0 is in the field of computational physics. The application of applied physics especially computational physics on textile science can be initiated in analyzing the quality of fabric in the textile coloring process.  This research focuses on a technique measuring the quality of fabric that occurred in the coloring process using the image processing technique by measuring the color space in the RGB (Red, Green, Blue) space as the length of colors vector of the fabric.  In this study, the technique has been made using MATLAB 2009a software and Logitech C525 HD webcam. The result of this research shows that computational physics especially image processing by MATLAB can be implemented to measure and to determine the color quality of fabric accurately by comparing with the samples.